2007
DOI: 10.1016/j.physa.2007.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Cellular automaton model for evacuation process with obstacles

Abstract: A bidimensional cellular automaton model is used to simulate the process of evacuation of pedestrians in a room with fixed obstacles. A floor field is defined so that moving to a cell with lower floor field means approaching an exit door. The model becomes non-deterministic by introducing a ''panic'' parameter, given by a probability of not moving, and by a random choice to resolve conflicts in the update of pedestrian positions. Two types of exit doors are considered: single (where only one person can pass) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
170
0
10

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 357 publications
(189 citation statements)
references
References 24 publications
1
170
0
10
Order By: Relevance
“…A field-based model defines the evacuation behavior of personnel at each simulated time point by defining the floor field of a scene and describing the flow trends of individuals in that scene [40][41][42][43]. The floor field relates to only the geometric layout and exit location of the room.…”
Section: Background and Motivationmentioning
confidence: 99%
“…A field-based model defines the evacuation behavior of personnel at each simulated time point by defining the floor field of a scene and describing the flow trends of individuals in that scene [40][41][42][43]. The floor field relates to only the geometric layout and exit location of the room.…”
Section: Background and Motivationmentioning
confidence: 99%
“…Agents can also be modeled individually with different characteristics to make them act independently and enhance the reliability of the system as a whole [25]. These characteristics are necessary to identify these agents as independent components of an application.…”
Section: Agent-based Modelmentioning
confidence: 99%
“…ViCrowd can be used to model different social groups (friends, family, etc.) in an easy way, which gives the simulation more flexibility in modeling social factors within the crowd simulation [25].…”
Section: Virtual Reality Lab (Vrlab)mentioning
confidence: 99%
“…In the study of Murosaki et al ,the fire spread model was advanced .It showed that the fire spread most strongly affect by the weather conditions and the building materials [5] .…”
Section: B Cell Characteristicsmentioning
confidence: 99%
“…The ti me t 1 is looked as the cell [kl] starts bur ning to when it began to spread of fire after catch fire. a is the len gth of one cell ,which usually is 4 m. d ,which is an un fixed vari able, will changes according to the time and condi tions [5,6] . For a given certain wind speed ,D is the fire can spread farthest distance, and calculated by [6] D =1.15(5 + 0.5V) (4) where V is the wind velo city.…”
Section: B Cell Characteristicsmentioning
confidence: 99%